Perancangan Rombong Multifungsi untuk Pedagang Kaki Lima - Venta Clariza Exstrilia; Grace Mulyono; Frenky Tanaya (Intra, 2018)
— People lifestyle interested street food is increasing. This can give innovation to the food cart development by providing functions such as tables and chairs that become united with the food cart. In addition, food cart can also be used indoors or outdoors.